HPV-Related Diseases: Strategies for Prevention - Hassan, Jamiyah (International Journal of Human and Health Sciences (IJHHS), 2024)
HPV Related Diseases: Strategies for Prevention" aims to provide comprehensive insights into human papillomavirus (HPV) and its related diseases (i.e., cervical cancer, genital warts, anal cancer). It discusses effective communication strategies to educate patients about safe practices and dispel misconceptions surrounding HPV. The presentation emphasizes the crucial role of healthcare professionals in advocating for early screening and detection of HPV infections, vaccination, and enabling timely intervention and treatment with the latest information. The talk will highlight the successful impact of prevention & vaccination strategies through evidence-based research. This will enhance medical professionals’ ability to protect patients from HPV-related diseases and improve overall public health outcomes. International Journal of Human and Health Sciences Supplementary Issue 01: 2024 Page: S12